The Effect of Planting Media and Types of Cutting Material on the Growth of Turnera subulata - Daulay, Ahmad Nasir; Gahara Mawandha, Hangger; Rosa Setyawati, Ety (Jurnal Pertanian, 2023)
The research was conducted at KP2 of the Institut Pertanian Stiper located in Maguwoharjo Village, Depok District, Sleman Regency, DIY. With an elevation of 118 mpl. The research was conducted from August 4, 2022, to November 1, 2022. The research was carried out using a factorial design that was arranged in a completely randomized design (CRD) and consisted of two factors. The first factor was the planting medium, which consisted of 4 levels: M0, regosol soil (control); M1, soil + cow manure (2:1); M2, soil + rice husk (2:1); and M3, soil + cow manure + rice husk (1:1:1). The second factor is the origin of the cutting material, which consists of 3 levels, namely the top of the segment (B1), the middle stem of the segment (B2), and the rootstock of the segment (B3), and each is 15 cm long. So that 4 x 3 = 12 combinations are obtained. Each treatment was repeated five times, resulting in the acquisition of 60 units. Experiment The research data were analyzed by analysis of variance (Anova) at the 5% level. If there is a significant effect, a DMRT follow-up test is carried out at the 5% level. The planting medium and cutting material interacted with plant height, number of shoots, number of leaves, fresh weight of roots, and dry weight of plants. Meanwhile, for fresh weight of plants, dry weight of roots, and leaf width, there was no interaction between the planting medium and the cutting material.